Penguatan Nilai-Nilai Akhlak dalam Pendidikan Agama Islam sebagai Upaya Pencegahan Bullying di Sekolah Menengah Atas - Mappanyompa, Mappanyompa; Sahwan, Sahwan; Aqodiah, Aqodiah; Pardi, M. Habib Husnial (State Islamic University of Mataram, 2025)
This Community Service Program (PKM) was implemented to address the urgency of increasing cases of bullying in schools, which have an impact on mental health, academic achievement, and the overall educational climate. This activity aims to: (1) increase students' understanding of the concept of bullying, its forms, and its impacts; (2) internalize Islamic moral values such as empathy, politeness, compassion, and brotherhood; (3) equip students with social skills in resolving conflicts wisely in accordance with the principles of Islamic Religious Education; (4) develop a child-friendly and bullying-free school culture; and (5) foster collective awareness to reject and prevent bullying. The PKM implementation methods included counseling, training, and conflict resolution practices, in collaboration with SMAN 1 Jonggat with 50 students participating. Evaluation was conducted through pre-tests, post-tests, and behavioral observations. The results of the activity showed an 80% achievement of the program objectives.